Retratos da arte e do artista: projeto autobiográfico de José Saramago - Marcon, Adriana [UNESP] (2014)
This dissertation proposes an analysis of Manual of Painting and Calligraphy (1977) and Memories of my Youth (2006), written by the Portuguese writer José Saramago, seeking to highlight their singularities, similarities and differences. It objectifies to show how the novel Manual of Painting and Calligraphy, for having autobiographical vestiges, is the sign of the portrayal of the art/ writing that will be put into practice in Saramago’s future writing, while Memories of my Youth, his autobiography, shows the portrayal of the artist/writer when his was young. With the choice of these books that represent, respectively, the beginning and the end of an autobiographical and literary project, it intends to consider the genre tensions installed in the autobiography when written by a novelist, as well as the presence of autobiographical vestiges in a novel. To reach this objective, it appeals to a theoreticalmethodological contribution based on specialists of Saramago’s writing, on reflections about novel and autobiography, and on studies of the structural analysis of narrative. After a long way of detailed reflections about the objects of this dissertation, it accomplishes the comparison between the narratives, evidencing the possible connections and differences between both texts